ChemInform Abstract: Conventional as well as Microwave Assisted Synthesis and Microbial Effect of Some New Acrylamides. Issue 20 (20th May 2014) - Kaur, Sandeep; Sharma, S.; Kaur, Jasvir; Sharma, Poonam
Abstract New acrylamides (III) and (V) possess poor antimicrobial activities and are ineffective growth inhibitors for fungis and yeasts.